A new species of Philetus Melander (Diptera: Empididae) from the Yukon Territory, Canada - Cumming, Jeffrey M.; Brooks, Scott E. (Zootaxa, 2020)
The Nearctic genus Philetus Melander, 1928 is a rarely collected group of empidid flies that contains two western species, namely P. memorandus Melander and P. schizophorus Melander. The genus was fully diagnosed by Cumming et al. (2016) with both known species redescribed and their distributions mapped. Here we describe a third species of Philetus from a single male collected recently in the Richardson Mountains of the Yukon Territory in Canada and provide a key to species based on male morphology. Terms used for adult structures follow those of Cumming & Wood (2017) and methods follow those outlined in Cumming et al. (2016).